Cryopreservation of ovine oocytes - Moawad, Adel Reda (2010)
Oocyte cryopreservation represents one of the most recent developments in the field of reproductive technologies. However, despite of significant progress, the efficiency of oocyte cryopreservation is still very low. Cryopreservation of mature metaphase II (MIl) oocytes has been reported to induce disorganization of the meiotic spindle and chromosome damage. However, cryopreservation of immature oocyte at germinal vesicle (GV) stage may provide an alternative which avoids these problems. Slow freezing protocols have more recently been replaced by vitrification approaches. In this thesis, recovery, viability and subsequent developmental potential following in vitro fertilisation (IVF), parthenogenetic activation or somatic cell nuclear transfer (SCNT) of ovine oocytes vitrified at GV stage and matured in vitro were studied. Solid surface vitrification (SSV) and cryoloop technologies share the advantages of using a containerless system and small volumes of solution (less than t J.ll) which favours rapid cooling. Maturation, fertilisation, cleavage and blastocyst development were significantly decreased in SSV vitrified oocytes as compared to controls. Following cryoloop vitrification, frequencies of in vitro maturation (43.4 vs 63.2%), oocytes with normal spindle and chromosome configuration (50.0 vs 70.4%) and fertilisation (54.0 vs 74. t %) did not differ significantly between vitrified and control oocytes. Numbers of cleaved embryos that developed to the blastocyst stage following IVM/IVF/IVC did not differ significantly between vitrified and control groups (29.4 vs 45.1 %). In vitro matured ovine oocytes vitrified at GV stage using cryoloop were activated by two different protocols (I) a combination of calcium ionophore (A 23187), cycloheximide and cytochalasin 13 (CA+CHX/CI3), (2) strontium and CB (Sr/Cll). No blastocysts developed in vitrified oocytes activated by CA+CHX/CB; however, 3.8% were obtained following Sr/CI3 activation. Developmental competence of ovinc oocytes vitrified at GV stage and used as cytoplast recipients for SCNT was evaluated. Although the frequencies of cleaved embryos were significantly decreased in vitrified oocytes as compared to control, development to morula and blastocyst stage embryos was not significantly different. No significant differences were observed in total cell numbers, number of apoptotic nuclei as detected by Hoechst and TUNEL assay and proportions of diploid embryos in day 7 blastocysts produced following IVF or seNT of vitrified oocytes as compared to control. Pre-treatment of ovine GV-oocytes with cytochalasin 13 (7.5 J.lglml for 60 min) or demecolcine (0.1 flg/ml for 20 min) prior to vitrification improved frequencies of maturation, fertilisation and subsequent development following IVF or parthenogenetic activation. Caffeine treatment during IVM (10 mM for 6 h) increased the frequencies of blastocyst development in vitrified/thawed GV ovine oocytes. Taken together, these studies suggest that, ovine oocytes vitrified at GV stage can be matured, fertilised and develop in vitro to blastocyst stage embryos. Cryoloop vitrification resulted in higher maturation, fertilisation and subsequent development as compared to SSV. Strontium can be used effectively for parthenogenetic activation of vitrified/thawed ovine GV oocytes. Ovine oocytes vitrified at GV stage can be used effectively as cytoplast recipients for SCNT.